RATING SCORE SPECIALIZED MEDICAL CARE PATIENTS RENAL PROFILE IN UKRAINE 2016 - M. O. Kolesnyk; N I. Kozlyuk; S. S. Nikolaenko (Ukrainian Journal of Nephrology and Dialysis, 2017)
Rating evaluation of specialized medical care for patients with renal deceases in Ukraine is conducted on basis of analysis of main criteria’s of its organization and availability, of results of treatment of CKD patients stage 5 HD, PD, T and AKI patients. Regional rating was evaluated separately for every group of parameters and then the summary rating evaluation was conducted